Effect of Perceived Usefulness, Ease of Use, Price Value, And Risk on Consumer Online Shopping Behavior Among Dangote Business School Students - Adamu Tako Mohammed,; Ahmad Audu Maiyaki,; Rabiu Hassan, (Research in Management of Technology and Business, 2024)
Internet is changing the buying behaviour of people across the globe. With technological advancement around the world, more people are increasingly becoming interested in conducting businesses over the internet. The aim of the study is to examine the determinants of consumer online buying behavior among Dangote Business Schools students. Specifically, the study investigates the effect of perceived usefulness, ease of use, price value, and risk on consumer online shopping behavior. Primary of data were used in conducting the study. The study implements a quantitative research design.  Data for the study were extracted through the use of structured questionnaire. A total of 272 questionnaires were distributed to the students of Dangote business school. Valid responses were analyzed with the aid of SPSS version 25 application. The study found a positive and significant relationship between perceived usefulness, perceived ease of use, perceived price value, perceived risk and consumer online buying behaviour among Dangote business school students, Kano State Nigeria. The study recommended that online sellers should provide website that provide seamless shopping experience, the ease of using the online sites, shopping attributes which directly increase the consumer behaviour towards the online shopping. The study also recommends that online vendors should implement strategies that guarantee riskless online payment processing and risk-free online shopping experience. Hence, the less risk perceived by consumers, the more likely they are to shop online.